Banking Policy and Macroeconomic Stability: An Exploration - Caprio, Gerard, Jr.; Honohan, Patrick (World Bank, Washington, D.C., 2013)
Whether and when does banking serve to stabilize the economy? The authors view the banking system as a filter through which foreign and domestic shocks feed through to the domestic economy. The filter can dampen or amplify the shocks through various credit market channels, including credit growth, import of foreign capital, and possibly interest rates. The question is whether the prudential quality of banking, as proxied by measures of regulatory quality and openness to foreign banking, amplify or dampen these shocks. The authors find that many of the regulatory characteristics that have been found to deepen a financial system and make it more robust to crises-notably those which empower the private sector-also appear to reduce the sector's ability to provide short-term insulation to the macro-economy. It is as if prudent bankers are reluctant to absorb short-term risks that, if neglected, might cause solvency and growth problems in the longer run. Forbearance might dampen short-term volatility, but at the expense of the longer run health of the banking sector and the economy. One way to avoid this apparent tradeoff is evident: banking systems which have a higher share of foreign-owned banks, a feature already associated with financial deepening and lowered risk of crisis, also seem to score well in terms of short-term macroeconomic insulation.